Building resilience against physical risk: the role of logistics performance in risk mitigation - Abroon Qazi (Geomatics, Natural Hazards & Risk)
This study examines the critical role of logistics performance in building resilience against physical risk, utilizing the FM Global Resilience Index—a composite measure of countries’ relative enterprise resilience to disruptive events—as a key benchmark. By applying a Bayesian Belief Network (BBN) modeling approach, data from 130 countries are analyzed, focusing on key risk factors such as climate risk quality, fire risk quality, and cybersecurity. The novelty of this research lies in its integration of logistics performance as a moderating factor within a probabilistic resilience model, which allows for the identification of how logistics alters the influence of different risk variables on national resilience—an approach not previously undertaken in resilience literature. The findings reveal strong interconnections between logistics performance and resilience, demonstrating that efficient logistics systems play a vital role in mitigating physical risks, particularly in fire safety and cybersecurity. This study provides valuable insights for policymakers and industry leaders to develop resilience strategies that reduce exposure to physical risks and enhance adaptability in an evolving risk landscape.